(untitled) (Journal of Dhaka Medical College, 2011)
Trends have been changed in poisoning in our country. Transport related poisoning is an emerging social and public health emergency in Bangladesh. As no remarkable studies has been done in this issue before, so there is no clear cut data about mode of poisoning. In this study it showed that the mode of poisoning is usually food with mixed benzodiazepines preparations. This prospective study was done in the Medicine unit of Sir Salimullah Medical College & Mitford Hospital, Dhaka, from July to December 2004. All the poisoning cases admitted in Medicine Unit of Sir Salimullah Medical College & Mitford Hospital, Dhaka are included in this study. A total 100 cases were studied. Among all the poisoning cases, ‘street poisoning’ by sedative hypnotic drugs were the highest percentage (37% of the total) and all were male. In males, 57.81% of poisoning caused by benzodiazepines (transport related poison), 20% by organophophorous, 3.12% by copper sulphate, 4.98% by benzodiazepines (attempted suicide), 4.98% by acid and 1.56% by kerosene. Among the female patients 41.66% of poisoning caused by organophophorous compounds, 19.44% by rat killer, 11.11 by coper sulphate, 8.33% by benzodiazepines, 5.55% by acid, 5.55% by savlon, 5.55% by herpic and 2.77% by phenol. Most of victims of street poisoning were businessman (67.56%) rest were normal/ domestic travelers (16.21%) and few were service holder (10.81%). Majority were from lower socio-economic classes. In analysis of the causes behind poisoning, 57% were due to familial disharmony/domestic trouble, 23% were poverty related, 15% were due to failure in affairs, 11% were due to failure in the examination, 4% were due to sexual abuse and 5% due to chronic illness and unknown cause. Key words: Poisoning; trends; street poisoning; socioeconomic condition. DOI: http://dx.doi.org/10.3329/jdmc.v20i1.8582 J Dhaka Med Coll. 2011; 20(1) :51-56